Genesis 14 - "n redaksie-kritiese ondersoek - Stoltz, Gerhard P. J. (HTS teologiese studies, 2001)
Genesis 14 - a redactio-critical analysis. This article focuses on Gen 14 as part of the Abraham narrative in Gen 12-25. Extant research showed that the form, style, and literary character of the chapter are not in congruence with the rest of the Abraham cycle. There are however, features that correspond well with other literary cycles in the Hebrew Bible, especially with Deuteronomistic literature. The consensus amongst scholars is that Gen 14 was originally not part of the Abraham cycle. The aim of this article is to argue from a redactiocritical perspective that Gen 14 should be regarded as an insertion in the Abraham narrative. The article concludes with a discussion ofthe socio-historical factors that played a role at the time of the interpolaion.